Comparison of efficacy between manipulation and exercise therapy in the treatment of patients with Sacroiliac joint dysfunction: A randomized clinical trial - Elyaspour, Dariush; Nikray, Rojin; Nouri, Farshad; Hashemi, Javad (Novelty in Biomedicine, 2020)
Background: Sacroiliac joint dysfunction is one of the main sources of lower back pain affects 16-30% of these patients. Various treatments had proposed for subluxation and sacroiliac syndrome but the current evidence on this subject is not confirmatory and few surveys have assessed the efficacy of manipulation in the treatment of this condition. The present study aimed to compare the efficacy of manipulation with exercise therapy in patients with sacroiliac pain syndrome. Materials and Methods: In this single-blinded clinical trial, the 30 patients categorized (to two groups) to receive either manipulation or exercise therapy. Required data gathered via medical history and the Persian translation of the Beck and Oswestry questionnaires and the pain assessed according to the visual analogue scale (VAS). Data entered into SPSS v.22 software for analysis. Results: Changes in VAS (p=0.011) and Oswestry score (p=0.012) after one week were significantly greater in the manipulation group. In addition, changes in the Oswestry disability index (ODI) score in the manipulation group of one week and one month after treatment were significantly different from the pre-treatment. Conclusion: Based on the findings of this survey, manipulation had a better efficacy on pain severity and disability of patients with sacroiliac pain syndrome, compared to exercise therapy and considering its low risks and non-invasiveness, its application by trained physicians recommended.